Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Effect of torrefaction severity on the energy recovery from amazonian wood residues for decentralized energy conversion systems - Edgar A. Silveira; Giulia Cruz Lamas; Pedro Paulo de O. Rodrigues; Normando P.B. Souto; Bruno Sant’Anna Chaves; Luiz Gustavo Oliveira Galvão; Lucélia A. Macedo; Juliana Sabino Rodrigues; Sandra M. Luz; Patrick Rousset; Thiago de Paula Protásio (Biomass and Bioenergy, 2025)

Irrigation in Jatropha curcas L. cultivation and its effect on biomass for bioenergy generation - Luis Filipe Cabral Cezario; Ananias Francisco Dias Júnior; Álison Moreira da Silva; Otávio Neto Almeida Santos; João Gilberto Meza Ucella-Filho; Thiago de Paula Protásio; Demetrius Profeti; Daniel Saloni; Patrick Rousset (Journal of Cleaner Production, 2023)

Stable coexistence of incompatible Wolbachia along a narrow contact zone in mosquito field populations - Célestine M. Atyame; Pierrick Labbé; François Rousset; Marwa Beji; Patrick Makoundou; Olivier Duron; Emilie Dumas; Nicole Pasteur; Ali Bouattour; Philippe Fort; Mylène Weill (Molecular Ecology, 2015)
In arthropods, the intracellular bacteria W olbachia often induce cytoplasmic incompatibility ( CI ) between sperm and egg, which causes conditional embryonic death and promotes the spatial spread of W olbachia infections into host populations. The ability of W olbachia to spread in natural populations through CI has attracted attention for using these bacteria in vector‐borne disease control. The dynamics of incompatible W olbachia infections have been deeply investigated theoretically, whereas in natural populations, there are only few examples described, especially among incompatible infected hosts. Here, we have surveyed the distribution of two molecular W olbachia strains ( w P ip11 and w P ip31) infecting the mosquito C ulex pipiens in T unisia. We delineated a clear spatial structure of both infections, with a sharp contact zone separating their distribution areas. Crossing experiments with isofemale lines from different localities showed three crossing types: w P ip11‐infected males always sterilize w P ip31‐infected females; however, while most w P ip31‐infected males were compatible with w P ip11‐infected females, a few completely sterilize them. The w P ip11 strain was thus expected to spread, but temporal dynamics over 7 years of monitoring shows the stability of the contact zone. We examined which factors may contribute to the observed stability, both theoretically and empirically. Population cage experiments, field samples and modelling did not support significant impacts of local adaptation or assortative mating on the stability of w P ip infection structure. By contrast, low dispersal probability and metapopulation dynamics in the host C x. pipiens probably play major roles. This study highlights the need of understanding CI dynamics in natural populations to design effective and sustainable W olbachia ‐based control strategies.